Outcomes of oesophageal self‐dilation for patients with refractory benign oesophageal strictures. Issue 1 (21st May 2018) - Qin, Y.; Sunjaya, D. B.; Myburgh, S.; Sawas, T.; Katzka, D. A.; Alexander, J. A.; Halland, M.
Summary: Background: Current management of refractory benign oesophageal strictures with endoscopic dilations and stenting leads to resolution of dysphagia in only 30% of patients. Oesophageal self‐dilation may be an alternative. Aim: To evaluate the efficacy and safety of oesophageal self‐dilation at a tertiary referral centre. Methods: We conducted a retrospective review of patients with refractory benign oesophageal strictures who participated in oesophageal self‐dilation at Mayo Clinic (Rochester, MN, USA) between 2003 and 2017. Clinical data including stricture characteristics, Dakkak and Bennett Dysphagia Score, number and dates of endoscopies, and complications were collected. A two‐tailed paired Student's t test was used to compare the measures of efficacy, with differences considered significant at a 5% probability level. Results: We identified 52 patients with refractory strictures treated with self‐dilation. The median number of endoscopic interventions was reduced from 9.5 (range 5‐30) to 0 (range 0‐3) within 12 months before and after self‐dilation, respectively ( P  < 0.0001). A median intervention‐free interval of 417 days (IQR 256‐756 days) was observed. The mean dysphagia score at baseline was 2.5 (95% CI 2.2‐2.8) and 0.33 (95% CI 0.11‐0.53) after self‐dilation. 23 of 27 (85%) patients who received enteral nutrition prior to self‐dilation had their feeding tubes removed. Conclusions: Oesophageal self‐dilation is an effective way of maintaining oesophageal patency in refractory benign oesophageal strictures, with safety comparable to current standard of care. Prospective studies are needed to further validate the role of self‐dilation in treatment of refractory benign oesophageal strictures.